Isolated annuloplasty in elderly patients with secondary mitral valve regurgitation: short- and long-term outcomes with a less invasive approach - Oezpeker, Ulvi Cenk; Hoefer, Daniel; Barbieri, Fabian; Gollmann-Tepekoeylue, Can; Johannes, Holfeld; Clemens, Engler; Suat, Ersahin; Adel, Sakic; Sasa, Rajsic; Mueller, Ludwig; Grimm, Michael; Bonaros, Nikolaos (Frontiers in Cardiovascular Medicine, 2023)
Background: Long -term outcomes of elderly and frail patients with secondary mitral valve regurgitation (MR) are inconclusive. Especially in patients with co-morbidities such as atherosclerosis, who are suffering from heart failure, optimal medical treatment (OMT) is the preferred therapy in relation to surgical or percutaneous interventions. It remains challenging to find the most successful therapy to improve symptoms and increase life expectancy. To reduce surgical trauma for the patients, minimally invasive mitral valve surgery (MIMVS) were developed with promising mid-term results, but there is still a lack of evidence on long-term results. The aim of this investigation is to describe the long-term results of less invasive mitral valve surgery (MVS) in elderly patients.In this longitudinal retrospective analysis, 67 patients (≥ 70 years) were identified, with secondary MR, who underwent MV repair ± tricuspid valve repair (TVR). MVS was performed via mini-thoracotomy (MT) (n=54) and in patients with contraindications for MIMVS, partial upper sternotomy (PS) (n=13) was the preferred surgical access. The appropriate access was chosen according clinical conditions and comorbidities. We analyzed reoperationfree long-term survival, combined operative-success (lack of residual MR, conversion to MVreplacement or larger thoracic incisions) and perioperative-safety (at 30-days: mortality, rethoracotomy, ECMO, pacemaker implantation, dialysis, longer ventilation, stroke, myocardial infarction). In a subgroup analysis, we compared long-term survival in MVS patients ± TVR.The median age of patients (62.7% female) was 74 years (interquartile range: 72-76 years) with a median EuroSCORE2 of 2.8% (1.5-4.6%) and N-terminal pro-brain natriuretic peptide plasma levels of 1434ng/l (1035-2149ng/l). The median follow-up was 5.6 years (2.7-8.5 years). The reoperation-free long-term survival up to 10 years was 66.2 %.Combined operative success and perioperative safety were reached in 94% and 76% of patients, respectively. Additionally TVR was performed in 56.7% of patients without significance in survival to the group without TVR (p= 0.417; HR 1.473, 95% CI 0.578-3.757).Less invasive MV-repair for secondary MR shows excellent operative success and safety in selected patients. Freedom from significant MR and need for reoperation demonstrates long-lasting efficacy. These results should be considered in heart-team discussions regarding patient allocation to surgical mitral procedures.